PENDAMPINGAN DIGITALISASI PEMBUKUAN DAN PENYUSUNAN LAPORAN KEUANGAN MELALUI APLIKASI AKUNTANSIKU PADA UMKM - Retno Dwi Saputri; Zaenal Wafa (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The main challenge faced by Micro, Small, and Medium Enterprises (MSMEs) is their limited capacity for financial administration, which is still conducted using conventional methods and lacks accountability. This community service initiative aims to equip MSMEs with the technical skills needed to operate the Akuntansiku application, facilitating the transition from manual bookkeeping systems to more accurate digital financial reporting. The method used is a participatory approach with direct mentoring through the stages of observation, mentoring, and evaluation. The results of the activity show that the mentoring process can facilitate MSME partners in digitally inputting transactions and independently compiling simple financial reports. The use of the application also helps make the process of recording and monitoring business finances more systematic. This activity demonstrates that guidance on bookkeeping digitization is crucial in supporting financial management and administrative compliance for MSMEs.